Mechanisms that enable the use of M&E information in decision-making to improve programme outcomes in the Centre for the Study of Violence and Reconciliation - Fanelwa, Lutshaba (University of the Witwatersrand, Johannesburg, 2024)
This study aims to show how employees employed by the Centre for Study of Violence and Reconciliation (CSVR) for a minimum of six months use M&E data to guide decision making choices and improve programme outcomes. To explore and appreciate the mechanisms and processes of decision-making using data from individuals collecting data and those making decisions in the organization, a research design used a case study through a qualitative method approach. One of the issues facing the NGO sector is the lack of documentation about the use of monitoring and evaluation data in decision-making procedures (Bornstein, 2006). Comprehending how gathered and processed data is used and how it improves programme outcomes is challenging because of this deficiency. The planned study will examine the various ways the organization uses data to make choices, as it is currently unclear if CSVR has the same conceptualization issues with data use and practice. The investigation results verified that the organization is faced with the same issue of inadequate documentation of its processes for monitoring and evaluation. This is made clear by the M&E framework, which provides insufficient information on database administration, information consumption, and routine data management activities. Using data and making decisions are related. The organization's decision-making process is not well understood; some people think decisions are made collaboratively by the team at weekly meetings, while others think project managers are in charge of making decisions. Decision-making and standardization in the application of knowledge are impossible without a functioning M&E system. The organizational structure makes it difficult to adopt an M&E system completely since it affects other programme support and where the unit fits in the organogram. M&E only provides support for one programme.
A research report submitted in fulfillment of the requirements for the Master of Management in Monitoring & Evaluation , In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Monitoring & Evaluation; M&E frameworks; Programme outcomes; SDG-8: Decent work and economic growth